Ode genre and ideological - artistic features of erkin vahidov’s odes - MUKHIDDINOV, MUSLIKHIDDIN; ISROIL SULAYMONOV; KHASANOVA, MASHKHURA; ASLANOVA, KHAFIZA; SHOMURODOVA, SITORA (The journal of contemporary issues in business and government, 2021)
This article gives information about the origin of the genre of ode, the history of Turkish ode, the creators of ode. It also provides theoretical information on the specifics of the ode genre, the content of the theme, the weight and the system of rhyme. Although ode is an ancient genre, it is still used in the works of our Devonian poets. In the offices of Erkin Vahidov we also find wonderful examples of this genre. This article discusses the ideological features of the poet’s poems “O’zbegim” (My Uzbek), “Inson” (Man), “Qo’llar” (Hands), the arts used in them, the system of rhyme and weight.